2020
DOI: 10.1021/jacs.9b13165
|View full text |Cite
|
Sign up to set email alerts
|

Highly Diastereoselective Functionalization of Piperidines by Photoredox-Catalyzed α-Amino C–H Arylation and Epimerization

Abstract: We report a photoredox-catalyzed α-amino C–H arylation reaction of highly substituted piperidine derivatives with electron-deficient cyano­(hetero)­arenes. The scope and limitations of the reaction were explored, with piperidines bearing multiple substitution patterns providing the arylated products in good yields and with high diastereoselectivity. To probe the mechanism of the overall transformation, optical and fluorescent spectroscopic methods were used to investigate the reaction. By employing flash-quenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(40 citation statements)
references
References 63 publications
3
37
0
Order By: Relevance
“…A reaction quantum yield of 0.15-0.3 is in good agreement with other studies on non-radical chain propagation reactions, where typical quantum yields of photoredox reactions can range from 0.19 to 0.43. [46][47][48] Ellman and coworkers partly explored the mechanism of a closely related α-amino arylation reaction involving substituted piperidine analogues and observed 0.4-0.6 at early timescales, 44 which is in relatively good agreement with our quantum yields. These results were collected without the use of insoluble sodium acetate, which may explain the higher quantum yield.…”
Section: Resultssupporting
confidence: 83%
See 2 more Smart Citations
“…A reaction quantum yield of 0.15-0.3 is in good agreement with other studies on non-radical chain propagation reactions, where typical quantum yields of photoredox reactions can range from 0.19 to 0.43. [46][47][48] Ellman and coworkers partly explored the mechanism of a closely related α-amino arylation reaction involving substituted piperidine analogues and observed 0.4-0.6 at early timescales, 44 which is in relatively good agreement with our quantum yields. These results were collected without the use of insoluble sodium acetate, which may explain the higher quantum yield.…”
Section: Resultssupporting
confidence: 83%
“…al. 33 and Walker et al 44 of 2.3 x 10 9 M -1 s -1 and 2.9 x 10 9 M -1 s -1 , respectively. By contrast, we did not observe quenching of the excited Ir(ppy) 3 when using NPP as the quencher, which again is in good agreement with McNally and coworkers.…”
Section: Electron Transfer Between Dcb and Ir(ppy)mentioning
confidence: 83%
See 1 more Smart Citation
“…Subsequently, Ellman and collaborators reported the α-amino CÀ H arylation of highly substituted piperidine derivatives 103 with electrondeficient cyanoarenes (entry 4, Scheme 20A). [49] Two transformations using cyanopyridines 100 as the feedstocks were examined; products were obtained in moderate yields and with high diastereoselectivities. Careful studies on the mechanism indicated that the diastereoselectivity of the CÀ H arylation was not good, but the slow epimerization was crucial to the final high diastereomer ratio.…”
Section: Azaarenes As Single-electron Oxidantsmentioning
confidence: 99%
“…iven the ubiquity of cyclic amines in a myriad of natural products and synthetic compounds, a growing emphasis has been placed on how we harness and manipulate such prestigious motifs for the construction of value-added molecules [1][2][3][4] . While significant progress has been made in the development of appending processes for their peripheral variation [5][6][7][8][9][10] , the skeletal diversification by means of ring-opening, -contraction, -expansion or -fusion approaches remains limited (Fig. 1a) 11 .…”
mentioning
confidence: 99%